Sanad Pengajar Al-Qur’an di Lembaga Tahfizh Al-Qur’an Kota Banjarmasin dan Sekitarnya (Studi Metode dan Jalur Periwayatan Sanad Al-Qur’an) - Fakhrie Hanief (Fakultas Ushuluddin dan Humaniora UIN Antasari Banjarmasin, 2023)
The Sanad of the Qur'an by memorizers of the Qur'an is considered as a guideline and legality (validity) in narrating the recitation of the Qur'an as well as part of efforts to maintain the purity of the Qur'an. There are so many memorizers of the Qur'an who have completed their memorization, but not many also have Qur'anic sanad with various causative factors. This sanad study was appointed as an important piece of information in the world of Al-Qur'an studies and even in the world of Al-Qur'an education. This research method is in the form of a literary method in the form of the original sanad of the owner by examining how the Al-Qur'an diploma method is used by memorizers of the Qur'an to get the Al-Qur'an isnad and how the transmission paths meet between the sanads they have. The results show that the ijaza method 'ardhan wa sam'an (depositing and listening to the teacher) occupies the highest degree, as does tahamul wal ada' with the same method' in hadith narration. Meanwhile, the path of transmission of the sanad al-Qur'an leads to the main qira'at priest, namely Imâm 'Âshim bin Abī Nujūd al-Kūfī, after the narration from the Prophet to a friend of r.hum.